Green synthesis of silver nanoparticles using Achillea biebersteinii flower extract and its anti-angiogenic properties in the rat aortic ring model - Baharara, Javad; Namvar, Farideh; Ramezani, Tayebe; Hosseini, Nasrin; Mohamad, Rosfarizan (MDPI AG, 2014)
Silver nanoparticles display unique physical and biological properties which have attracted intensive research interest because of their important medical applications. In this study silver nanoparticles (Ab.Ag-NPs) were synthesized for biomedical applications using a completely green biosynthetic method using Achillea biebersteinii flowers extract. The structure and properties of Ab.Ag-NPs were investigated using UV-visible spectroscopic techniques, transmission electron microscopy (TEM), zeta potential and energy dispersive X-ray spectrometers (EDS). The UV-visible spectroscopic analysis showed the absorbance peak at 460 nm, which indicates the synthesis of silver nanoparticles. The average particle diameter as determined by TEM was found to be 12 ± 2 nm. The zeta potential analysis indicated that Ab.Ag-NPs have good stability EDX analysis also exhibits presentation of silver element. As angiogenesis is an important phenomenon and as growth factors imbalance in this process causes the acceleration of several diseases including cancer, the anti-angiogenic properties of Ab.Ag-NPs were evaluated using the rat aortic ring model. The results showed that Ab.Ag-NPs (200 μg/mL) lead to a 50% reduction in the length and number of vessel-like structures. The synthesized silver nanoparticles from the Achillea biebersteinii flowers extract, which do not involve any harmful chemicals were well-dispersed and stabilized through this green method and showed potential therapeutic benefits against angiogenesis.